Lightweight surveillance systems on embedded domains - Tan, Jun Han (Nanyang Technological University, 2022)
Surveillance systems are prevalent and pervasive in modern society with applications spanning across multiple sectors such as safety, security, healthcare and many more. With the exponential growth in technology, research has been geared towards computer-based deep neural network techniques for complex tasks that require a lot of resources. However, as the need for these systems grows, the crucial element of form factor and cost comes into play. This paper presents a comprehensive review on the development of such applications on a low cost, small form factor device – Himax WE-I Plus.